Hubungan Antara Status Pemberian Asi Dengan Perkembangan Motorik Kasar Pada Bayi Usia 7-12 Bulan Di Desa Tohudan Kecamatan Colomadu Kabupaten Karanganyar - FAUZIYAH, Yoda; , Dyah Widowati, SKM; , Listiana Dhemawati, M.Si (2015)
Background: Exclusive breastfeeding is breastfeeding without any additional food and drink in infants age zero to six months and the water is not given in the stage of exclusive breastfeeding. One of the factors that influence the development of the child is a nutritional factor. Breast milk contains all the nutrients needS for optimal growth and development of children. Breast milk contains taurine a form of albumin which is only find in breast milk.Taurine serves as a neuro transmitter and plays an important role for the maturation process of the brain cells. One infant development can be optimized is the motor development. Purpose: Was knowing correlation between the exclusive breastfeeding with gross motor development in infants aged 7-12 months. Method of the Research: The research was implementing a surveyobservationalwith cross-sectional approach. Subject of the research was 40 individuals selecting by used non probability sampling. Data identity of pregnant women and exclusive breastfeeding was taking by used a interview and questionnaire. Data was analyzing by used correlation test of Chi-square. Result: Most mothers can not breastfeed the child by 60,0% and most of the motor development of children including the appropriate category of 57,5%. Conclusion: there was correlation between the exclusive breastfeeding with gross motor development in infants aged 7-12 months at Colomadu's Public Health Center of Karanganyar Regency